Milk's inorganic content analysis via laser induced breakdown spectroscopy. (1st May 2023) - Nanou, Eleni; Stefas, Dimitrios; Couris, Stelios
Graphical abstract: Highlights: LIBS for the determination of milk's elemental composition. LIBS study of liquid milk, lyophilized and ashed milk. Optimum experimental conditions for detecting Ca, Na, K, Mg, Cu, Si, P. Good correlation of the LIBS results with atomic absorption measurements. Abstract: In the present work, the inorganic content of different milk samples is investigated by Laser Induced Breakdown Spectroscopy (LIBS) technique. Milk samples of different animal origin, in liquid, lyophilized powder, and ashed forms were studied using both infrared (1064 nm) and visible (532 nm) laser excitation conditions and the optimum experimental conditions for the measurement of the inorganic elements present in low concentration, were determined. Spectral features of major (Ca, Na, Mg and K) and minor minerals (P, Zn, Cu and Si) were detected and identified. The LIBS results for the different milk samples were found to correlate perfectly with the results obtained from atomic absorption measurements, demonstrating the potential of LIBS technique for the fast and in-situ qualitative characterization of the inorganic content of different animal origin milk samples.